Charleston and the Great Depression : a documentary history, 1929-1941 - Taylor, Kieran Walsh (The University of South Carolina Press, 2018)
"Charleston and the Great Depression tells many stories of the city during the 1930s--an era of tremendous want, hope, and change--through a collection of forty annotated primary documents. Included are letters, personal accounts, organizational reports, meeting minutes, speeches, photographs, oral history excerpts, and trial transcripts. Together they reveal the various ways in which ordinary lowcountry residents--largely excluded from formal politics--responded to the era's economic and social crises and made for themselves a 'New Deal'"--